2020
DOI: 10.25259/sni_189_2020
|View full text |Cite
|
Sign up to set email alerts
|

A case of dual three-column thoracic spinal fractures following traumatic injury

Abstract: Background: Thoracic spine fracture-dislocations due to motor vehicle accidents (MVAs) rarely involve double- level, noncontiguous lesions. Case Description: A 19-year-old male following an MVA was paraplegic; he exhibited full motor/sensory loss below the T4 level (i.e., ASIA scale Grade A). The chest X-ray, magnetic resonance, and computed tomography studies confirmed T3–T5 and T11–12 fractures, warranting T3–L3 thoracolumbar decompression and fusion. Despite surgical intervention, the patient’s neurolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 5 publications
0
16
0
4
Order By: Relevance
“…7 Double-level three-column injuries have been reported more recently in the literature with a primary focus on fracture dislocations. [8][9][10][11][12] Few reports have been released in the literature focusing on purely double-level Chance fracture. 13,14 The typical mechanism of injury for Chance fractures is attributed to an MVA, where the individual experiences rapid deceleration while wearing a lap seat belt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Double-level three-column injuries have been reported more recently in the literature with a primary focus on fracture dislocations. [8][9][10][11][12] Few reports have been released in the literature focusing on purely double-level Chance fracture. 13,14 The typical mechanism of injury for Chance fractures is attributed to an MVA, where the individual experiences rapid deceleration while wearing a lap seat belt.…”
Section: Discussionmentioning
confidence: 99%
“…14,19,20 Our case complements the recent reports recommending more extensive fixation for severe multilevel spinal injuries, based on the outcomes experienced by our patient. 8,9…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It is a rare but devastating spinal injury secondary to highenergy trauma. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Patients with TTS are at increased risk for significant vascular injury, hemodynamic instability, and spinal cord injury. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Adequate reduction and stabilization allow for early mobilization and rehabilitation.…”
mentioning
confidence: 99%
“…1 It is a rare but devastating form of spinal injury typically due to high-energy trauma such as motor vehicle crush, or less commonly from lower-energy trauma such as a fall in patients with severe osteoporosis. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Patients with TTS are at a greater risk for vascular injury, hemodynamic instability, and spinal cord injury. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, sufficient reduction and stabilization can facilitate early mobilization and rehabilitation.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, sufficient reduction and stabilization can facilitate early mobilization and rehabilitation. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The authors of the current study 19 performed a systematic review of surgical management of TTS patients from 1983 to 2021 using Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Individual Patient Data (PRISMA-IPD) guidelines with 2 independent reviewers. 20 The authors identified 17 articles with a total of 38 patients with TTS managed surgically.…”
mentioning
confidence: 99%